Exploring thermochemical pressing in the manufacture of TiN - W cermet-based composite materials - Y. Belokon; O. Hrechanyі; T. Vasilchenko; D. Kruglyak (International Journal of Thermofluids)
One of the most promising areas in the field of obtaining new materials with a high level of operational characteristics is the creation of powder refractory alloys based on cermets using high-energy and high-speed pressure processing methods. Such technologies include thermochemical pressing technology. The focus of the investigation was on TiN–W cermet, which is the end result of the reaction. A notable characteristic of the Ti + W system is the occurrence of contact melting of tungsten, a refractory material, at the boundary of phase separation during the formation of the primary structure. Through thermogravimetric studies, it has been observed that the cermet composed of TiN + W remains resistant to oxidation even at elevated temperatures up to 655 °C. After a full heating and cooling cycle, the mass gain was 10 %. The results obtained allow optimizing the technological process conditions to achieve the desired properties of cermets, such as hardness, strength, wear resistance, and thermal stability.